QUALITY CONTROL OF MODERN MEDICAL LINEAR ACCELERATORS - Y. V. Tsitovich; I. G. Tarutin; M. G. Kiselev (Приборы и методы измерений)
The necessity of methods and devices for modern medical linear accelerators quality control development is discussed. Quality control is the basic measure of radiation protection of the patients with malignant tumors during radiotherapy. Linear accelerators devices and systems which are influencing on  accuracy of dose delivery and dose distribution within treated patients body volumes were considered. Developed methods and devices become a basis of the national protocol for medical linear accelerators quality control which will be used in all oncological clinics of Belarus Republic.